Manufacturing of halal pharmaceuticals - Ahmad, Kausar (IIUM Press, 2015)
This book aims to cover the fundamental aspects of pharmaceutical manufacturing from the Islamic worldview to inspire students that whatever they do including very mundane routine work such as checking pH can be an ‘ibādah - if they work within the sphere of Islamic teachings and in shā’ Allah all the time and effort will be rewarded by Allah SWT. The first chapter describes the Islamic perspectives towards the safeguarding of life vis-à-vis the use of medicines or pharmaceuticals and can be considered as an overview for the Islamic manufacturing practices. Although this book is about the manufacturing of pharmaceuticals, other industries may benefit from the discourse and examples given. As much as possible, processes and regulations are described in the book so that it covers the syllabus of industrial pharmacy for undergraduate use and still can be referred for postgraduate studies.